2022
DOI: 10.1039/d1fo03671h
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive improvement effect of nervonic acid and essential fatty acids on rats ingestingAcer truncatum Bungeseed oil revealed by lipidomics approach

Abstract: The oil of Acer truncatum Bunge seed (ASO) is rich in ω-9 (53.93%) and ω-6 (30.7%) fatty acids (FAs), and characterized by 3-7% nervonic acid (NA, C24:1ω-9). Evidence suggests that...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 68 publications
1
30
1
Order By: Relevance
“…As reported in Table 1, we identified and quantified 18 FAs in the ASO, and noticed that 88.96% of the FAs were unsaturated, including 58.47% monounsaturated fatty acids (MUFA). In accordance with earlier research, 16,17,21 our findings showed that the top five FAs in the ASO were linoleic acid (28.21%), oleic acid (21.83%), lysergic acid (19.99%), cis , cis -11-eicosenoic acid (8.59%), and NA (8%). Also, the content of ω-3, 6, 9 in the ASO were ω-3 FAs (1.48%), ω-6 FAs (29.01%) and ω-9 FAs (58.41%), respectively.…”
Section: Resultssupporting
confidence: 92%
“…As reported in Table 1, we identified and quantified 18 FAs in the ASO, and noticed that 88.96% of the FAs were unsaturated, including 58.47% monounsaturated fatty acids (MUFA). In accordance with earlier research, 16,17,21 our findings showed that the top five FAs in the ASO were linoleic acid (28.21%), oleic acid (21.83%), lysergic acid (19.99%), cis , cis -11-eicosenoic acid (8.59%), and NA (8%). Also, the content of ω-3, 6, 9 in the ASO were ω-3 FAs (1.48%), ω-6 FAs (29.01%) and ω-9 FAs (58.41%), respectively.…”
Section: Resultssupporting
confidence: 92%
“…More and more studies show that nervonic acid benefits neurological health (Wadhwani et al, 2011; Li et al, 2019) and has therapeutic potential for adrenoleukodystrophy and multiple sclerosis (Lewkowicz et al, 2019; Terluk et al, 2022). Moreover, nervonic acid levels in specific tissues are associated with Alzheimer’s disease (Astarita et al, 2011), Parkinson’s disease (Hu et al, 2021), cognition (Song et al, 2022), mood symptoms (Kageyama et al, 2018; Kageyama et al, 2021), cardiovascular death (Delgado et al, 2017) and even obesity (Keppley et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Nervonic acid is crucial for nerve myelin synthesis, which is one of the fundamental components of the nerve and brain ( Poulos, 1995 ; Merrill et al, 1997 ; Martínez and Mougan, 1998 ). It has been found that nervonic acid is essential for developing the human nervous system and can be used to prevent and treat various neurodegenerative diseases ( Kageyama et al, 2021 ; Song et al, 2022 ; Terluk et al, 2022 ). However, long-term exposure to excessive levels of erucic acid can reduce the β-oxidation of erucic acid in animal myocardia, leading to lipid deposition and tissue damage ( Bremer and Norum, 1982 ).…”
Section: Introductionmentioning
confidence: 99%